The genus Micandra Staudinger (Lepidoptera: Lycaenidae: Theclinae) in Colombia, with the description of a new species from the Sierra Nevada de Santa Marta - Prieto, Carlos (Zootaxa, 2011)
Micandra stephanieae, sp. nov., is described and illustrated from the Sierra Nevada de Santa Marta in northern Colombia. Adult specimens and male genitalia are illustrated and compared with those of M. aegides (C. Felder & R. Felder) and M. dignota (Draudt), the putatively most closely related species. A synopsis of the Micandra species in Colombia is presented along with distribution maps and a key to the species based on wing pattern.